SARS-CoV-2 effective breeding number estimation in Vitória de Santo Antão/PE, Brazil (Research, Society and Development, 2020)
COVID-19 is an acute respiratory disease with the SARS-CoV-2 virus as etiological agent, triggering a worldwide pandemic of severe acute respiratory syndrome (SARS) from the year 2019. Effective reproduction number expresses the viral spread potential, being favourable in determining the epidemiological outbreak behaviour; and in obtaining crucial information to identify the disease intensity and which interventions should be conducted. The study objective was to analyze COVID-19 transmissibility, in Vitória de Santo Antão/PE, municipality, Brazil. Therefore,  and , indicators were estimated, which reflect the effective number of SARS-CoV-2 infection reproduction among the Vitória de Santo Antão/PE population, within 107 days from the first confirmed case (covering the disease history to date). Results showed that, to date, measures have been sufficient to effectively reduce the epidemic transmissivity. However, even with slower epidemic growth, the population must remain alert and maintain social distance in order to flatten the curve. In addition, estimates can be understood correctly and therefore enable decisions to be made to help more efficiently control pandemic expansion.